Factors Influencing Tiktoker's Purchasing Intention In Malaysia - Mohammad Asyraf, Mohammad Nazir (2024)
This study explores comprehensively into the multifaceted factors that shape the purchasing decisions of Malaysian TikTok users, focusing keenly on three pivotal variables: influencer endorsement, advertisement, and user engagement manifested through commentary and reviews. In the ever-evolving landscape of social media, TikTok stands out as a dynamic platform where trends shift rapidly, and user-generated content dominates. Understanding the nuanced interplay been these elements is essential for marketers and businesses aiming to leverage the platform effectively. Employing a rigorous quantitative approach, the study embarks on a jney to glean insights from the behaviors and preferences of 442 active TikTok users across Malaysia. Through an intricately designed survey questionnaire, data is meticulously collected to dissect the impact of influencer endorsements, advertisement, and engagement on the purchasing inclinations of TikTok's vibrant community. TikTok influencers wield considerable influence as opinion leaders, shaping trends and consumer perceptions. This research endeavors to unravel the mechanisms through which influencer endorsements resonate with users, engender trust, and ultimately influence purchasing decisions. Moreover, the study extends its focus to user engagement, manifested through commentary and reviews. User-generated content serves as a cornerstone of TikTok's appeal, fostering a sense of community and facilitating organic interactions. By dissecting the dynamics of user engagement, this research endeavors to elucidate its impact on purchasing behavior, highlighting the significance of community-driven interactions in shaping consumer preferences and decisions. By delving deep into influencer endorsement dynamics, assessing the efficacy of advertisement strategies, and unraveling the nuances of user engagement, the research aims to offer valuable insights for marketers and businesses seeking to navigate the complexities of TikTok's vibrant ecosystem The outcomes of this research not only enhance the understanding of TikTok as a porful e- commerce platform but also offer practical implications for marketers, influencers, and businesses aiming to optimize their strategies for engaging the Malaysian consumer market through TikTok.